Population genomics of local adaptation versus speciation in coral reef fishes (Hypoplectrus spp, Serranidae). Issue 7 (26th February 2016) - Picq, Sophie; McMillan, W. Owen; Puebla, Oscar
Abstract: Are the population genomic patterns underlying local adaptation and the early stages of speciation similar? Addressing this question requires a system in which (i) local adaptation and the early stages of speciation can be clearly identified and distinguished, (ii) the amount of genetic divergence driven by the two processes is similar, and (iii) comparisons can be repeated both taxonomically (for local adaptation) and geographically (for speciation). Here, we report just such a situation in the hamlets ( Hypoplectrus spp), brightly colored reef fishes from the wider Caribbean. Close to 100, 000 SNPs genotyped in 126 individuals from three sympatric species sampled in three repeated populations provide genome‐wide levels of divergence that are comparable among allopatric populations ( F st estimate = 0.0042) and sympatric species ( F st estimate = 0.0038). Population genetic, clustering, and phylogenetic analyses reveal very similar patterns for local adaptation and speciation, with a large fraction of the genome undifferentiated ( F st estimate ≈ 0), a very small proportion of F st outlier loci (0.05–0.07%), and remarkably few repeated outliers (1–3). Nevertheless, different loci appear to be involved in the two processes in Hypoplectrus, with only 7% of the most differentiated SNPs and outliers shared between populations and species comparisons. In particular, a tropomyosin ( Tpm4 ) and a previously identified hox ( HoxCa ) locus emerge as candidate loci (repeated outliers) for local adaptation and speciation, respectively. We conclude that marine populations may be locally adapted notwithstanding shallow levels of genetic divergence, and that from a population genomic perspective, this process does not appear to differ fundamentally from the early stages of speciation. Abstract : We compare the population genomic patterns of local adaptation versus speciation in the hamlets ( Hypoplectrus spp, Serranidae), a group of brightly colored reef fishes from the wider Caribbean. We show that the population genomic patterns are broadly similar for the two processes, but with different loci involved. We identify Tpm4, a tropomyosin, as a candidate locus for local adaptation in the hamlets.